Mould pressing magnetic conductive slot wedge and preparation method thereof
Through the preparation method of molded magnetic permeable wedges, the combination of pretreated iron powder, epoxy resin adhesive and glass fiber cloth is used to solve the problems of reduced insulation resistance and insufficient mechanical strength of magnetic permeable wedges in high temperature and high pressure environments, and efficient and reliable magnetic permeable wedge preparation is achieved.
Patent Information
- Application Number
- CN202411809214.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-15
AI Technical Summary
The existing magnetic permeable wedges tend to reduce insulation resistance in high temperature and high pressure environments, resulting in a decrease in motor efficiency and shortened service life. At the same time, their mechanical strength and magnetic conductivity are insufficient, and there are problems of layering and edge weaknesses.
By using the preparation method of molded magnetic permeable wedge, a magnetic permeable wedge with high insulation resistance, mechanical strength and magnetic permeability are prepared by coating pretreated iron powder and epoxy resin adhesive on a glass fiber cloth, and baking and rolling molding.
It improves the insulation resistance, mechanical strength and magnetic conductivity of the magnetic slot wedge, enhances its tolerance in high temperature and high pressure environments, extends the service life of the motor, and improves the efficiency and reliability of the motor.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of motors, and more specifically, relates to the preparation of a molded magnetically conductive slot wedge with higher insulation resistance. Background Art
[0002] With the development of economy and the progress of society, energy issues have become increasingly prominent. The energy consumption of motors accounts for a large proportion of the total social energy consumption. The high-end motor manufacturing industry pays more and more attention to the application of magnetic slot wedges to improve the efficiency and performance of motors.
[0003] The stator (rotor) core of the motor generally has open coil slots to embed the coils. The slot wedges are the key materials used to fix the coils and close the slots. Commonly used slot wedges are made of insulating materials, so the distribution of the air gap magnetic field in the core slot is uneven, which will generate excitation current, pulsation and surface loss, causing the core and winding temperature to rise. The coil slots also increase the effective air gap length of the motor core, increase the excitation reactive power, reduce the power factor and efficiency of the motor, and increase the noise of the motor.
[0004] Using magnetic wedges instead of insulating slot wedges can make the air gap magnetic field uniform, reduce the excitation current, reduce the core loss, improve the power factor, and improve the motor efficiency. At the same time, it can reduce the motor temperature rise and reduce electromagnetic noise and vibration, thus extending the motor's service life. According to data, after using magnetic slot wedges, the motor's no-load current drops by 10-13%, iron loss decreases by 30-40%, temperature rise decreases by 8-15℃, efficiency increases by 1.6-3.7%, and noise decreases by 10-15 decibels.
[0005] The laminated magnetic wedges of various shapes made by cutting, grinding and other mechanical processing techniques of laminated magnetic plates (or laminated magnetic strips) are currently the most important types of magnetic wedges. The laminated magnetic plates used are generally made according to the following process: the thermosetting resin adhesive and the alkali-free glass fiber cloth are impregnated or coated and then dried, the glued glass cloth obtained is cut and stacked in multiple layers, and magnetic powder (mainly iron powder) is added between the two layers of glass cloth during stacking, and then hot pressed into a magnetic plate. For example, the invention patent CN102218861A provides a method for manufacturing a laminated magnetic plate, in which the glass cloth is first coated with a silane coupling agent, and then coated with an adhesive solution composed of silicone resin, polyester resin, etc., and then dried and cut, and magnetic powder is added to the glass cloth, and then hot pressed at 200-220°C for 2-5 hours.
[0006] The laminated magnetic slot wedge has poor interlayer bonding strength, and the processing technology of the laminated magnetic slot wedge will cut the reinforcing glass cloth and expose the edge weaknesses, which can easily cause local slot wedges or iron powder to fall into the motor, causing short-circuit damage to the motor coil.
[0007] There are molded magnetic slot wedge products abroad. Because molded magnetic slot wedges do not need to go through cutting, grinding and other processing processes, the slot wedge structure is complete, the overall strength is high, there is no delamination and edge weakness, and it has better application reliability.
[0008] Other magnetic wedges, such as pull-out magnetic wedges and magnetic mud, are rarely used nowadays due to their poor strength and frequent accidents.
[0009] Obviously, the mechanical strength and magnetic conductivity of the magnetic slot wedge are the most important. With the increase of the rated voltage of the new motor, the insulation resistance index of the magnetic slot wedge has been paid more and more attention. Because when the motor is operating normally, the alternating main magnetic flux and leakage magnetic flux pass through the magnetic slot wedge, which will produce hysteresis and eddy current loss. The adhesive of the magnetic slot wedge may be thermally aged due to heat. The magnetic slot wedge will also be affected by the force of the magnetic field current, and even resonance will occur. This phenomenon of causing the temperature rise and force of the magnetic slot wedge seriously affects the service life of the magnetic slot wedge, but this effect will be greatly reduced with the increase of the insulation resistance of the magnetic slot wedge. Considering that the magnetic material is often conductive, therefore, how to improve the existing magnetic slot wedge to improve its mechanical strength and magnetic permeability while improving the insulation resistance of the magnetic slot wedge is particularly important.
[0010] The contact parts between the laminated magnetic slot wedge and the motor core are all cut and ground processing surfaces. The motor industry generally recommends using the cone pin electrode method in 5.3.3 of GB / T 1408.1-2016 to measure the insulation resistance between the processing surfaces. When the laminated magnetic plate is manufactured, the upper and lower surfaces are generally covered with glass cloth with good insulation, while the magnetic powder between the layers is relatively concentrated. If the test is carried out according to the method of 5.2.1 plate or sheet material in GB / T 1408.1-2016, the volume resistivity may be 10 8 -10 12 Ω·cm, or even higher. When tested by the cone pin electrode method (or the method of setting electrodes on both end surfaces), the insulation resistance value is small, generally equal to 0. Summary of the invention
[0011] An object of the present invention is to provide a method for preparing a molded magnetic slot wedge, which gives the magnetic slot wedge excellent mechanical strength, magnetic permeability and insulation resistance, good heat resistance and high reliability, and is suitable for use in high-efficiency motors, high-voltage motors, explosion-proof motors and other high-end motors.
[0012] Another object of the present invention is to provide a wrapping molding method to improve the mechanical strength of the magnetic slot wedge.
[0013] Another object of the present invention is to provide a wrapping molding method to reduce the defects of magnetically conductive slot wedges.
[0014] Another object of the present invention is to provide a pre-treated iron powder to improve the insulation resistance of the magnetic wedge.
[0015] To achieve the above object, the present invention adopts the following technical solutions:
[0016] A molded magnetic wedge is prepared by coating an epoxy resin adhesive and pre-treated iron powder according to the following weight parts on a glass fiber cloth and baking the coated cloth;
[0017] 60-75 parts of pretreated iron powder;
[0018] Epoxy resin adhesive (solid content) 15-40 parts;
[0019] 5-30 parts of mixed solvent;
[0020] 8-16 pieces of fiberglass cloth;
[0021] The adhesive tape is cut and rolled, and then placed in a mold for hot pressing to prepare a molded magnetic conductive slot wedge.
[0022] The pretreated iron powder is an iron powder that has been surface treated with a treatment liquid.
[0023] Furthermore, the treatment process of the pre-treated iron powder is as follows: the treatment liquid is sprayed onto the iron powder, the iron powder should be turned over during the spraying process to facilitate uniform mixing, and then dried at 50-130°C.
[0024] Furthermore, the treatment liquid is an ethanol solution containing the following substances:
[0025] Inorganic acid 0.5-3%
[0026] Zinc naphthenate 0.1-1%
[0027] Silane coupling agent 0.01-1%
[0028] Phosphate 0.1-2%.
[0029] Preferably, the inorganic acid is hydrochloric acid.
[0030] Preferably, the silane coupling agent is Degussa 2926 water-based coupling agent.
[0031] Preferably, the phosphate ester is inositol hexaphosphate.
[0032] Furthermore, the iron powder is reduced iron powder, and its fineness is 50-300 mesh.
[0033] Preferably, the reduced iron powder has a fineness of 200 mesh.
[0034] Furthermore, the ratio of the iron powder to the treatment liquid is 100:3-10 (parts by weight).
[0035] The epoxy resin adhesive is a thermosetting heat-resistant epoxy resin adhesive.
[0036] Preferably, the epoxy resin adhesive is TJ1461 heat-resistant epoxy adhesive (produced by Zhuzhou Times Insulation Materials Co., Ltd.).
[0037] The mixed solvent is a mixed solvent of toluene, acetone, ethanol, propylene glycol ethyl ether, etc., and is used to adjust the viscosity of the epoxy adhesive.
[0038] The glass fiber cloth is 100 g / m 2 Alkali-free glass fiber cloth.
[0039] Furthermore, the baking temperature for making the adhesive tape is 100-150° C., and the baking time is 3-10 minutes.
[0040] Preferably, the baking conditions of the adhesive tape should be such that the solvent content of the adhesive tape is less than 1%, the adhesive tape is in an appropriate degree of hardness and semi-cured state, and the oven temperature is generally controlled at 110-170°C and the baking time is 5-15 minutes. The preferred baking conditions for TJ1461 epoxy adhesive are 130°C±5°C for 10-15 minutes.
[0041] The preparation method of the magnetic conductive slot wedge is as follows:
[0042] The adhesive tape is cut to the required size, rolled into a round rod, inserted into the molding mold, and then the mold is closed; the molding mold is pressed tightly in a flat hot press machine, the hot pressing molding temperature is 150-200℃, and the hot pressing time is not less than 30 minutes; after cooling and demoulding, the surface is cleaned and the finished product is cut according to the product length. The finished product will be similar to Figure 1 In the cross section, the glass fiber is impregnated and completely covered by the epoxy resin cured material.
[0043] The present invention has found through experiments that the surface of the pre-treated iron powder has a similar Figure 3 In the structure shown, the molded magnetic wedge made of pre-treated iron powder has a higher insulation resistance value.
[0044] Compared with the existing magnetic slot wedge preparation technology, the present invention has the following significant beneficial effects and advantages:
[0045] (1) The present invention provides a molded magnetic slot wedge having the characteristics of complete and uniform structure, high overall strength, good magnetic conductivity, etc. The outer surface of the slot wedge is protected by an epoxy adhesive layer and is not easy to fall off, thereby solving the problems of easy delamination and processing edge weaknesses of existing laminated magnetic slot wedges, and significantly improving the reliability of use.
[0046] (2) The present invention provides a special wrapping molding method, so that the glass cloth in the cross section of the prepared magnetic slot wedge exists in a curved and crossed form without a layered surface, which can significantly improve the bending strength and splitting resistance of the slot wedge.
[0047] (3) The present invention provides a method for pretreating magnetic conductive powder. The prepared magnetic conductive slot wedge not only maintains excellent magnetic conductivity and strength, but also greatly improves insulation resistance. It is suitable for high-voltage motors, traction motors, wind power and other special motors with higher rated voltages, and produces better effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is a micro CT image of the cross section of the rolled molded magnetic groove wedge.
[0049] Figure 2 It is a micrograph of reduced iron powder
[0050] Figure 3 It is a micrograph of pre-treated iron powder. DETAILED DESCRIPTION
[0051] In order to make the technical personnel in the technical field better understand the scheme of the present invention, the technical scheme in the embodiment of the present invention will be clearly and completely described in combination with the drawings in the embodiment of the present invention. Obviously, the described embodiment is only an embodiment of a part of the present invention, rather than all embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work should belong to the scope of protection of the present invention, and the reagents or materials used in the present invention are commercially available unless otherwise specified.
[0052] Example 1
[0053] This embodiment provides a molded magnetic slot wedge, which is prepared by coating epoxy resin adhesive and pre-treated iron powder on glass fiber cloth, baking to remove the solvent to make a top adhesive cloth, cutting and rolling the top adhesive cloth and placing it in a mold for hot pressing to form a molded magnetic slot wedge. The specific method is as follows:
[0054] (1) Stir 20 g of hydrochloric acid, 5 g of zinc cyclohexaneate, 5 g of 2926 coupling agent, 10 g of inositol hexaphosphate, and 960 g of ethanol at room temperature to prepare a treatment solution. Spray 500 g of the treatment solution evenly onto 10 kg of 200-mesh reduced iron powder, and stir the iron powder repeatedly. Place the iron powder with the treatment solution evenly on the surface, and bake it in an oven at 100°C for 1 hour until it is dry to obtain pretreated iron powder.
[0055] (2) 30.8 parts of TJ1461 epoxy glue with a solid content of 60% and 10 parts of mixed solvent were stirred evenly at room temperature, mixed with 68 parts of pre-treated iron powder and evenly coated on 12 parts by weight of alkali-free glass fiber cloth (standard weight 100 g, product of Jushi Co., Ltd.). Then, it was baked in a drying oven at a temperature of 130℃±5℃ for 12 minutes to obtain a glued glass fiber cloth with a solvent content of 0.7%.
[0056] (3) The adhesive tape is cut to the required size, rolled into a round rod, inserted into the molding mold, and then the mold is closed. The molding mold is pressed on a flat hot press, and the hot pressing molding temperature condition is 170°C and the hot pressing time is 40 minutes. After cooling and demolding, the product is surface-finished and cut into finished products according to the product length requirements to obtain molded magnetic wedges.
[0057] The finished molded magnetic wedge will look like this: Figure 1 The cross section shown in the figure shows that the glass fiber is impregnated and completely covered by the epoxy resin curing material; the entire or partial surface of the pre-treated iron powder has a similar Figure 3 The structure shown in the figure shows that the molded magnetic wedge made of pre-treated iron powder has a higher insulation resistance.
[0058] Example 2
[0059] Comparative Example 1, when preparing the pre-treated iron powder, the treatment liquid was reduced by 50%, and the molded magnetic wedges were prepared under the same other conditions.
[0060] Example 3
[0061] Compared with Example 1, the amount of glass cloth is reduced by 2 parts, and the amount of TJ1461 epoxy glue is increased accordingly. That is, the second step is: 36.6 parts of TJ1461 epoxy glue with a solid content of 60% are stirred and mixed with 8 parts of mixed solvent at room temperature, mixed with 68 parts of pre-treated iron powder and evenly coated on 10 parts by weight of alkali-free glass fiber cloth (standard weight 100 g, product of Jushi Co., Ltd.). Then, it is baked in a drying oven controlled at 130℃±5℃ for 12 minutes to obtain the glued glass fiber cloth, and the molded magnetic guide slot wedge is prepared under the same other conditions.
[0062] Example 4
[0063] Comparative Example 1, the reduced iron powder was not pretreated, and other conditions were the same to prepare the molded magnetic slot wedge.
[0064] Example 5
[0065] Comparative Example 1, the fineness of the iron powder was changed to 100 mesh, and the molded magnetic slot wedges were prepared under the same other conditions.
[0066] Example 6
[0067] Comparative Example 1, the fineness of the iron powder was changed to 300 mesh, and the molded magnetic slot wedges were prepared under the same other conditions.
[0068] Example 7
[0069] Comparative Example 1, the inorganic acid in the treatment solution was changed to nitric acid of the same concentration, and other conditions were the same to prepare the molded magnetic wedge.
[0070] Example 8
[0071] Comparative Example 1, the amount of pretreated iron powder was changed from 68 parts to 58 parts, and other conditions were the same to prepare the molded magnetic slot wedge.
[0072] Example 9
[0073] Comparative Example 1, the amount of pretreated iron powder was changed from 68 parts to 80 parts, and other conditions were the same to prepare the molded magnetic slot wedge.
[0074] Comparative Example 1
[0075] Imported molded magnetic wedge product, product model: SPInduwedge F (HP), manufacturer: ASPIN
[0076] Comparative Example 2
[0077] A typical domestic laminated magnetic slot wedge product, product model: F889H, manufacturer: Beijing Xinfulunda Insulation Materials Co., Ltd.
[0078] Example 10
[0079] According to GB / T 1033.1 Determination of density of non-foamed plastics Part 1: Immersion method, liquid pycnometer method and titration method, the density of the sample was tested; according to GB / T 1303.4-2005 Test method for bending properties of fiber reinforced plastics, the bending strength of the sample was tested; according to GB / T 3217-2013 Magnetic test method for permanent magnetic (hard magnetic) materials, the relative magnetic permeability of the sample was tested; according to 5.3.3 cone pin electrode method of GB / T 1408.1-2016, the insulation resistance of the sample was measured; according to GB / T1410-2006 Test method for volume resistivity and surface resistivity of solid insulating materials, the volume resistivity of the sample was tested. The test results of Examples 1-9 and Comparative Examples 1-2 are shown in Tables 1 and 2.
[0080] Table 1 Performance test data of Examples 1-9 and Comparative Examples 1-2
[0081] Table 2 Comparison of product performance between Example 1 and Comparative Examples 1-2
[0082] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the solution. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents based on the understanding of the present solution without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A molded magnetic slot wedge, characterized in that: The adhesive cloth is prepared by coating epoxy resin adhesive and pre-treated iron powder according to the following weight parts on the glass fiber cloth, and then baking to remove the solvent; 60-70 parts of pretreated iron powder; Epoxy resin adhesive (solid content) 15-40 parts; 10-30 parts of mixed solvent; 8-16 pieces of fiberglass cloth; The adhesive tape is cut and rolled, and then placed in a mold for hot pressing to prepare a molded magnetic conductive slot wedge.
2. The molded magnetically conductive slot wedge according to claim 1, characterized in that: The adhesive tape is rolled into a circular rod shape, put into a forming mold, and pressed into a molded magnetic conductive slot wedge through hot pressing.
3. The molded magnetically conductive slot wedge according to claim 1, characterized in that: The temperature condition of the hot pressing molding is 150-220°C.
4. The molded magnetically conductive slot wedge according to claim 1, characterized in that: The pretreated iron powder is obtained by treating the surface of the iron powder with a treatment liquid.
5. The molded magnetically conductive slot wedge according to claim 4, characterized in that: The treatment process of the pre-treated iron powder is as follows: the treatment liquid is sprayed onto the iron powder, the iron powder should be turned over during the spraying process to facilitate uniform mixing, and then dried at 50-130°C.
6. The molded magnetically conductive slot wedge according to claim 4, characterized in that: The treatment liquid is an ethanol solution containing the following substances: Inorganic acid 0.5-3% Zinc naphthenate 0.1-1% Silane coupling agent 0.01-1% Phosphate 0.1-2%.
7. The molded magnetically conductive slot wedge according to claim 4, characterized in that: The ratio of the iron powder to the treatment liquid is 100:3-10 (parts by weight).
8. The molded magnetically conductive slot wedge according to claim 4, characterized in that: The iron powder is reduced iron powder, and its fineness is 50-300 meshes.
9. The molded magnetically conductive slot wedge according to claim 1, characterized in that: The epoxy resin adhesive is a thermosetting heat-resistant epoxy resin adhesive.
10. The molded magnetically conductive slot wedge according to claim 1, characterized in that: The glass fiber cloth is 100 g / m 2 Alkali-free glass fiber cloth.
11. The molded magnetically conductive slot wedge according to claim 6, characterized in that: The inorganic acid in the treatment liquid is hydrochloric acid.
12. The molded magnetically conductive slot wedge according to claim 6, characterized in that: The silane coupling agent is a water-soluble silane coupling agent, preferably Degussa 2926 water-based coupling agent.
13. The molded magnetically conductive slot wedge according to claim 6, characterized in that: The phosphate ester is inositol hexaphosphate.
14. The molded magnetically conductive slot wedge according to claim 1, characterized in that: The baking temperature for making the adhesive tape is 100-150° C., and the baking time is 3-10 minutes.
Citation Information
Patent Citations
Double high laminated concentrating flux plate and preparation method thereof
CN102218861A